Origins of Systemic to Pulmonary Collateral Arteries and their Relative Frequencies in Patients with Pulmonary Artery Atresia or Stenosis as determined using Multidetector Computed Tomography Angiography - Smith, Mark Royden (Division of Radiology, 2019)
INTRODUCTION: Critical to the management of pulmonary atresia (PA) or pulmonary stenosis (PS) is accurate and comprehensive knowledge of the vascular network supplying the lungs. This vascular network can be exceedingly complex as it may include a wide variation of systemic to pulmonary collateral arteries (SPC/s). AIM: This study aims to guide radiologists, cardiologists and cardiothoracic surgeons in their search for SPC/s and to recommend an accurate, informative and standardised nomenclature system for SPC/s based on the relative frequency of SPC/s origins in patients with PA or PS identified using multi-detector computed tomography arteriography (MDCTA). METHOD: In this retrospective descriptive study a data set was created incorporating MDCTA cases performed at Red Cross War Memorial Children’s Hospital, Cape Town, South Africa (RCWMCH) during the period November 2013 to November 2017. Using multiple, temporally separated readers, cases with PA or PS were identified and further analysed for systemic to pulmonary circulation collateral supply, including patent ductus arteriosus (PDA) and SPC/s with special attention given to their origins and destinations. RESULTS: Of 145 eligible MDCTAs, 93 demonstrated PA or PS of which 31 demonstrated systemic to pulmonary circulation collateral supply, 17 with a PDA, 19 with a single SPC/s, 5 with both a PDA and SPC/s and 14 with multiple SPC/s. The majority of SPC/s originated from the descending aorta, however, there were numerous other intra- and extrathoracic systemic arterial vessels of origin. CONCLUSIONS: The recommended systematic search pattern for systemic to pulmonary circulation collateral supply as determined by their relative frequencies of origin should be for a PDA first, then for SPC/s originating from the descending aorta (DA), aortic arch (AArch), left subclavian artery (LSCA) and right subclavian artery (RSCA). However, SPC/s may arise from numerous other sources and no systemic artery can be neglected. “Systemic to pulmonary collateral artery/s” (SPC/s) is a more accurate general term than “major aortopulmonary artery/s” (MAPCA/s), as 40% of SPC/s do not originate from the aorta. The large variability in location of SPC/s makes a classification system impractical and favours descriptive characterization, the simplest form of which must include the origin and destination of each SPC/s, for example (DA to Left main pulmonary artery (LMPA)) or (AArch to right main pulmonary artery (RMPA)).